The Effectiveness of 3D Animation Video Media on Science Learning Interests of Class III Students - Helena Cristine Paulina Marbun; Ainur Rosyid (PT FORMOSA CENDEKIA GLOBAL, 2023)
Interest is a condition where someone has attention and interest to do something. Lack of student involvement and interest in learning can occur because the learning media used by teachers cannot attract students' attention. The research conducted at SDN Grogol 05 aims to find out whether 3D animation video media is effective in increasing interest in learning science in grade III students. This type of research is quantitative, using an experimental research model with a true experimental research design post-test only control group with questionnaires used as data collection instruments. The results showed that the average score for the treated class interest was 93.14, while the average score for students without treatment was 83.04. Based on independent measurements, the test sample obtained a significance value of 0.000 < 0.05 so that the use of 3D animated video media affects the significance which means that students' interest in learning increases, and there is a difference between the interest in learning experimental and control classes. So from this study, it was concluded that the use of 3D animation video media is effective in increasing the interest in learning science of grade III students